Yayun Farm Business Development Strategy Using SWOT and AHP Analysis - Sabillah, Jadid Abda; Wardhana, Danu Indra; Setiawan, Andika Putra (Universitas Muhammadiyah Jember, 2024)
Jember Regency has laying chicken egg in 2021 amounting to 12,223,473/kg, Balung District became the highest egg producing area reaching 2,235,266/kg. In the following year, productivity increased, and the production of laying chicken eggs in 2022 amounted to 12,251,219/kg. Balung District still become the district with the highest egg production in Jember which amounted to 2,240,340/kg. Yayun Farm is one of the small-scale laying breed chicken farming businesses in Balung District which has been running for a long time and has a high commercial value, namely the large consumer demand for eggs. However, Yayun Farm still experienced several problems in developing its business. So the purpose of this study is to find out internal and external factors, alternative strategies, and strategic priorities in developing the Yayun Farm business. The results of the research in the SWOT analysis stated that the position of Yayun Farm is located in quadrant I, where the chosen strategy is the Strength/Opportunities (SO). With limited resources to implement alternative strategies simultaneously, AHP analysis is carried out to find strategic priorities from alternative strategies obtained from SWOT. The priority of the strategy selected with the highest weight is to improve and maintain product quality and quantity (0.667371852). The implementation of this strategy aims to maximize the potential possessed by Yayun Farm, even though there are limited development funds, farm operations can still develop and become better.